2016
DOI: 10.1371/journal.pone.0163670
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free Systems Based on CHO Cell Lysates: Optimization Strategies, Synthesis of “Difficult-to-Express” Proteins and Future Perspectives

Abstract: Nowadays, biotechnological processes play a pivotal role in target protein production. In this context, Chinese Hamster Ovary (CHO) cells are one of the most prominent cell lines for the expression of recombinant proteins and revealed as a safe host for nearly 40 years. Nevertheless, the major bottleneck of common in vivo protein expression platforms becomes obvious when looking at the production of so called “difficult-to-express” proteins. This class of proteins comprises in particular several ion channels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 72 publications
1
52
0
Order By: Relevance
“…For complex proteins, eukaryotic CF systems are ideal as they contain the endogenous microsomes derived from the endoplasmic reticulum (ER), enabling co-translational translocation of proteins and ER-based PTMs [10,11,18,19]. There has been a constant improvement in the quality of lysate preparation, system optimization, linear templatebased protein synthesis, and reduction of process costs, which has led to the preparation of cost-effective systems suitable for commercial purposes.…”
Section: Cell-free Protein Synthesis Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…For complex proteins, eukaryotic CF systems are ideal as they contain the endogenous microsomes derived from the endoplasmic reticulum (ER), enabling co-translational translocation of proteins and ER-based PTMs [10,11,18,19]. There has been a constant improvement in the quality of lysate preparation, system optimization, linear templatebased protein synthesis, and reduction of process costs, which has led to the preparation of cost-effective systems suitable for commercial purposes.…”
Section: Cell-free Protein Synthesis Systemsmentioning
confidence: 99%
“…Toxic proteins may be difficult to synthesize [16] Membrane proteins Suitable for a wide range of MPs of different sizes MP overexpression can lead to cell toxicity and death [17][18][19] Membrane protein solubilization To solubilize MPs, supplements can be added directly to the reaction mixture in the form of nanodiscs, detergents or liposomes (prokaryotic systems and wheat germ systems) or by using endogenous microsomes or proteoliposomes (eukaryotic sys-…”
Section: Cell-free Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…CHO cell lysates were chosen, since they had previously been established as the most productive eukaryotic system in our hands [24], while concomitantly enabling a direct comparison to the production of hBMP2 in cell line 4D6. Previous observations have shown that adding specific circular DNA templates (plasmids) to CHO cell-free protein synthesis systems instead of linear DNA, may further increase protein yields [49]. When added to the cell-free reaction mixture, the PCR product (for details see Fig.…”
Section: Production Of Hbmp2 In a Cell-free Mammalian Expression Systemmentioning
confidence: 99%
“…This corresponds to a 20-fold increase in protein yield compared to the best results from the cell-based expression systems. Previous observations have shown that adding specific circular DNA templates (plasmids) to CHO cell-free protein synthesis systems instead of linear DNA, may further increase protein yields [49]. To exclude any background translational activity of the lysates, a blank control, lacking the supplemented DNA, was prepared.…”
Section: Production Of Hbmp2 In a Cell-free Mammalian Expression Systemmentioning
confidence: 99%